Investigação biológica e química de actinobactérias da Amazônia isoladas no campus da UFAM da rizosfera de Inga edulis - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
Actinobacteria are recognized as prolific producers of natural products (NPs) of biotechnological interest. These cosmopolitan microorganisms are the main sources of antimicrobials and, in the first decades of the 21st century, they have emerged as possible new sources of non-antimicrobial NPs of medicinal and agroindustrial interest. Prospecting for these microorganisms in the most diverse ecosystems has revealed new species that stand out in screenings with activities, namely: antimicrobial, anticancer, larvicidal and antiparasitic, among others. In this context, the development of this doctoral thesis had the general objective of isolating actinobacteria from the rhizosphere of Inga edulis Martius – (Mart.), a legume endemic to the Amazon region and present on the campus of the Federal University of Amazonas (UFAM); and evaluating their biotechnological potential in a spectrum of biological assays, such as: antifungal, anticancer, antimalarial and larvicidal. We also aim to perform genome mining of “Biosynthetic Gene Clusters” (BGCs) related to PN synthesis and identify chemical substances related to biological activities. This thesis is divided into three chapters: In Chapter 1, we present a review published in the journal “Antonie van Leeuwenhoek (Springer Nature)”. In it, we describe the biotechnological potential of actinomycetes in the 21st century, starting with their antimicrobial activities and ending with their potential to remediate substances harmful to the environment. In Chapter 2, we present a total of 64 isolates of actinobacteria from the rhizosphere of three I. edulis Mat. plants and a screening, using the paired culture method, with 20 selected strains that are capable of attenuating the mycelial growth of the following phytopathogens: Colletotrichum sp. (ISO01), C. guaranicola (P01), Pestalotiopsissp. (3002R2), Conynespora cassiicola (Iso079) and Sclerotium coffeicola (M01). Molecular analyses of the 16S rRNA gene of the 20 strains classified them into two genera: Streptomyces (90%) and Kitasatospora (10%). Among these, two strains were selected for the production of extracts, fractions and bioguided fungal antibiosis assays: Streptomyces sp. (LaBMicrA B270) did not show antibiosis for S. coffeicola (M01) and Streptomyces sp. (LaBMicrA B280) was efficient against all phytopathogens. The best results were obtained with the liquid medium fraction AcOEt/2-propanol 9:1. LabMicrA B270 showed fungicidal activity with the EtOAc/2-propanol 9:1 fraction at a minimum dosage of 250 µg/mL against the four phytopathogens. LabMicrA B280 showed fungicidal activity with the EtOAc/2-propanol 9:1 fraction at a minimum dosage of 250 µg/mL for S. coffeicola and 125 µg/mL for the other phytopathogens. These results prove that both strains have potential to be used as biocontrol agents, as well as sources of substances with fungicidal activity. In chapter 3, we present a biological and chemical study of the extracts produced by the LabMicrA B280 strain. Morphological analyses by scanning electron microscopy show that this strain presents pseudomycelial ornamentations similar to species of the genus Streptomyces. In the phylogenomic analysis, its digital hybridization value between DNAs (dDDH) is <70%, 63.6%, which defines it as a new species of the genus Streptomyces, and the analysis of its chemical profile by APCI/MS shows ions without equivalence in the PN databases. The genome of LabMicrA B280 has 8.2 Mb, distributed in 96 contigs, with a G+C content of 72%, N50 of 229,434, and occurrences of 314 subsystems, with 24 gene categories. The genomic mining analyses resulted in seven BGC annotations that present 100% similarity out of a total of 39 BGCs. Among these, the BGC related to the synthesis of pentamycin, an antifungal that was also isolated from the ME/AP/RF3 fraction of LabMicrA B280, stands out. The best results in the biological assays were observed for this fraction with: 125 µg/mL minimum dosage against S. coffeicola (M01) and 62 µg/mL against the other phytopathogens; 50 µg/mL minimum dosage for 91.45% ± 0.55 cytotoxicity against human laryngeal epithelioma (HEp-2) cancer cells, with no cytotoxic effect against healthy cells; antiplasmodial activities with minimum dosages of 50 µg/mL against the W2 and 3D7 strains of Plasmodium falciparum with mortality effects of 91.3% ± 0.03 and 61.0% ± 0.18; and 250 µg/mL larvicidal dosage to achieve 100% mortality against Aedes egypti. From this fraction, the substance pentamycin, a potent fungicide used in the treatment of vulvovaginal candidiasis, was also isolated. The biotechnological spectrum of the new species LabMicrA B280 shows that the Amazon is home to actinobacteria with great biotechnological potential. This unprecedented work investigated the biological activities of actinobacteria isolated from the rhizosphere of I. edules, and presented promising results for the control of phytopests, biological control of A. egypti and P. falciparum, and secondary metabolites with important medicinal activities (anticancer and antifungal).
Keywords: Plantas - Efeito dos fungicidas; CIENCIAS BIOLOGICAS; Potencial biotecnológico; Actinobactérias; Identificação molecular; Mineração genômica; Atividades biológicas